Innovative technologies tackling food loss - Galanakis, Charis M.; Oksen, Peter (World Intellectual Property Organization, 2020)
This edition of the Global Challenges in Focus series explores cutting-edge technologies to reduce food loss in the supply chain. Though identifying "critical loss points", the brief proposes innovative technologies with the highest estimated impact on mitigating food loss. To continue the topic of the food management process, a forthcoming paper will address the technologies tackling food waste.
Keywords: Food industry and trade -- Technological innovations.; Food waste.; Food supply.